Badger Ballistics Participation in WSGC Collegiate Rocket Launch 2016 - Zeugner, David William (Proceedings of the Wisconsin Space Conference, 2017)
This paper is a report of Badger Ballistics’ participation in the Collegiate Rocket Launch competition hosted by the Wisconsin Space Grant Consortium. The objective of this competition is to build a high power rocket depicting an accurate scale model of a launch vehicle used by private industry or government, and predict its launch apogee with minimal error. The vehicle’s target apogee must fall between 2500 and 3500 feet. The team chose to create a rocket replicating the German V-2 look. Most unique to our design is our use of 3D printing for body components. At competition day, the team submitted an apogee prediction of 3300 feet and recorded an unofficial launch apogee of 2940 feet. Badger Ballistics achieved the third closest apogee prediction and placed fifth overall in competition.